2009
DOI: 10.1386/jdsp.1.2.215_1
|View full text |Cite
|
Sign up to set email alerts
|

Written in the body: reflections on encounters with somatic practices in postgraduate dance training

Abstract: This article tracks my exploration of the somatic practices as a postgraduate dance student, set against the background of my previous experience and my journey to this place through conventional dance training. Personal reflections and journal writings are combined with a more formal definition and discussion of the somatic practices and their application to dance training and performance, with particular reference to the Alexander Technique and Body-Mind Centering. What emerges is a personal record of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Future research needs to establish interventions that enable coping and continued success. Past studies support this as they highlight that good self-awareness increased the chances of career success [ 40 , 41 ]. Dancers identified that being able to take risks with suffering and injury was important, and this resulted in working at the limit of the body, which could produce meaningful goals and the continuation of their career.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Future research needs to establish interventions that enable coping and continued success. Past studies support this as they highlight that good self-awareness increased the chances of career success [ 40 , 41 ]. Dancers identified that being able to take risks with suffering and injury was important, and this resulted in working at the limit of the body, which could produce meaningful goals and the continuation of their career.…”
Section: Discussionmentioning
confidence: 90%
“…Further studies can explore why some dancers are able or unable to distinguish performance and injury pain and if having this ability would cultivate better pain behaviours towards injury. Self-awareness and self-management skills for injuries are critical factors for increased career success [ 40 , 41 ] and can facilitate a pathway towards continued performance. Further studies should explore the factors that may facilitate this transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatics can also help break "the mindset that if [dancers] are not sweating or hurting… they are going to lose technique" (Roche & Huddy, 2015, p. 156, emphasis in original). Previous research has shown that somatic training has benefitted contemporary dancers: it increased awareness (Allen, 2009;Fortin & Girard, 2005;Fortin et al, 2009;Rouhiainen, 2008;Weber, 2009), enabled a more holistic view of oneself that considers both body and mind (Fortin & Girard, 2005), and encouraged improvements in technique through versatility and articulacy (Allen, 2009;Weber, 2009). Dancers have also gained confidence (Weber, 2009), greater authority, and respect for their bodies (Fortin et al, 2009) through somatic training.…”
Section: Review Of Literaturementioning
confidence: 99%